2010
DOI: 10.1128/jvi.02078-09
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Influenza Virus Infection and Pathology

Abstract: A key question in pandemic influenza is the relative roles of innate immunity and target cell depletion in limiting primary infection and modulating pathology. Here, we model these interactions using detailed data from equine influenza virus infection, combining viral and immune (type I interferon) kinetics with estimates of cell depletion. The resulting dynamics indicate a powerful role for innate immunity in controlling the rapid peak in virus shedding. As a corollary, cells are much less depleted than sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
303
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(311 citation statements)
references
References 48 publications
(63 reference statements)
7
303
0
1
Order By: Relevance
“…3A) for the process of within-host clearance of MeV RNA and fitted these models to the quantitative measurements acquired from the macaque experiments (28)(29)(30). We considered three nested models, which take different components of the immune system into account.…”
Section: Resultsmentioning
confidence: 99%
“…3A) for the process of within-host clearance of MeV RNA and fitted these models to the quantitative measurements acquired from the macaque experiments (28)(29)(30). We considered three nested models, which take different components of the immune system into account.…”
Section: Resultsmentioning
confidence: 99%
“…the limit of detection or 1 infectious particle. See the original studies and also Li & Handel [52] [83]. The latter was assumed to represent symptoms.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…Other than the model by Smith et al [29], we are not aware of any other experimentally confirmed model of the progression of S. pneumoniae. There are, however, several proposed models for influenza [31,51,52]. Of these, the model developed by Handel et al [28] is best suited for our purposes for three key reasons: (i) in contrast to models based on human [30] or equine [31] influenza, the model by Handel et al is based on a murine challenge system, with which all experiments on viral -bacterial interactions are studied; (ii) it explicitly considers innate immunity; and (iii) it is statistically fitted to experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several proposed models for influenza [31,51,52]. Of these, the model developed by Handel et al [28] is best suited for our purposes for three key reasons: (i) in contrast to models based on human [30] or equine [31] influenza, the model by Handel et al is based on a murine challenge system, with which all experiments on viral -bacterial interactions are studied; (ii) it explicitly considers innate immunity; and (iii) it is statistically fitted to experimental data. That said, we have explored the robustness of our findings to alternative formulations of the Handel et al model, concerning the shape and strength of interference (electronic supplementary material, figure S6) and the potential dependence of immune response on viral load (electronic supplementary material, figure S7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation